Lipschütz Ulcer associated with SARS-CoV-2 infection - a case report - Simões,Joana da Cunha (2023)
Abstract Lipschütz ulcer (LU) is a diagnosis of exclusion, characterized by the sudden appearence of deep, wide and painful vulvar ulcers associated with a non-sexually transmited infectious disease. We describe a case of a woman with fever, myalgias and odynophagia associated with SARS-CoV-2 infection and deep, painful vulvar ulcers in a kissing pattern. She did topic corticosteroids and lidocaine treatment and had a complete resolution. No other cause for the vulvar ulcers was found. We found four other similar cases in recent literature. LU is often underdiagnosed, and the aim of the article is to highlight the possibility of this diagnosis in a patient with COVID-19 after exclusion of other possible causes.